Matarieh, la Sainte Famille et les baumiers - Zanetti, Ugo (Analecta Bollandiana, 1993)
According to Egyptian tradition, the Holy Family rested at Maṭariyya, a place near Cairo, on their Flight to Egypt. Thousands of pilgrims went there to see the tree which split to shelter the Holy Family, the well where the Virgin dipped her Son, the balsam-tree which grew there watered by this holy well; the pilgrims, Copts and others, prayed and celebrated the eucharist on the stone which was believed to have been used by Mary to care for her Child. An examination of the Christian Arabic texts related to this place - and especially Abū l-Makārim's chronicle, yet unused - together with some others (Muslim Arabic, Russian or Latin travel narratives) sheds some fresh light on the history of this pilgrimage place. The accounts of the balsam-tree as found in the various sources are given in an Appendix.